2017
DOI: 10.1093/bja/aex338
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of changes in lactate concentration with intravascular microdialysis during high-risk cardiac surgery using the trend interchangeability method

Abstract: NCT02296593.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Intravenous microdialysis has previously been used to evaluate metabolites (e.g., lactate, glucose, pyruvate, and creatinine) [ 8 , 16 , 17 , 18 , 19 , 20 ], antibiotics (e.g., glycopeptides, aminoglycosides, and cephalosporins) [ 5 , 6 , 21 ], and antifungals (e.g., fluconazole) [ 22 ]. Studies investigating metabolites have primarily reported lower metabolite concentrations obtained by intravenous microdialysis in comparison to standard plasma sampling [ 16 , 17 , 18 , 19 , 20 ], although one study found a good correlation [ 21 ]. For flomoxef and fluconazole, comparable concentrations were found with the two sampling methods [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Intravenous microdialysis has previously been used to evaluate metabolites (e.g., lactate, glucose, pyruvate, and creatinine) [ 8 , 16 , 17 , 18 , 19 , 20 ], antibiotics (e.g., glycopeptides, aminoglycosides, and cephalosporins) [ 5 , 6 , 21 ], and antifungals (e.g., fluconazole) [ 22 ]. Studies investigating metabolites have primarily reported lower metabolite concentrations obtained by intravenous microdialysis in comparison to standard plasma sampling [ 16 , 17 , 18 , 19 , 20 ], although one study found a good correlation [ 21 ]. For flomoxef and fluconazole, comparable concentrations were found with the two sampling methods [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%